Non-pharmacological pain management practice and barriers among nurses working in Debre Tabor Comprehensive Specialized Hospital, Ethiopia. - Shegaw Zeleke (Public Library of Science (PLoS), 2021)
Background Pain is an unpleasant sensory and emotional experience associated with or resembling that actual or potential tissue damage. Different study findings show that about 55% to 78.6% of inpatients experience moderate-to-severe pain. Nurses are one of the health professional who may hear of pain suffered by the patients and who can manage patient suffering by themselves. Therefore, their correct skill is very important in non- pharmacology and pharmacology pain management methods. Objective To assess non-pharmacological pain management practice and barriers among nurses working in Debre Tabor Comprehensive Specialized Hospital, Ethiopia. Methods Data were collected using structured observational check list with interviewer administered questionnaires that measure nurses' practice on non-pharmacological pain management. Data were entered using Epi Data version 3.1 and analyzed using SPSS (Stastical Package for Social Sciences) version 23. Bivariable and multivariable analysis were conducted to examine the association between independent and outcome variables. Results A total of 169 nurses participated in the study, with a response rate of 100%. Among the study participants 94 (55.6%) were females, and the mean age of nurses were 34.9(SD = 5.7) years. Only 44(26%) of nurses had good practice on non- pharmacology pain management methods. About 130(77.55%), 125(74.0%), and 123(72.8%) of nurses reported that inadequate cooperation of physicians, multiple responsibilities of nurses and insufficient number of nurses per patient ratio as barriers for practice of non -pharmacology pain management respectively. Conclusion Majority of nurses didn't apply non-pharmacological pain management practices for their patients in pain and the overall practice level of nurses was very poor. The major identified obstacle factors for the poor practice of non-pharmacological pain management methods were nurses' fatigue, inadequate cooperation of physicians, heavy workload, multiple responsibilities of nurses, and insufficient number of nurses per patient ratio and unfavorable attitude of nurse on non-pharmacology pain management. Even if nurses experiences different challenges, they shall use non-pharmacological pain management methods complementary to pharmacological treatment of pain as they are low cost and safe. And also boosting nurse's attitude towards the effect of non-pharmacological pain management methods is crucial.